KOMPARASI PENERAPAN MODEL STAD DAN TGT TERHADAP HASIL BELAJAR DAN AKTIVITAS SISWA (STUDI PADA SISWA KELAS V MATA PELAJARAN PKN DI SDN BENDO 1, KEC. PARE, KAB. KEDIRI) - Aka, Kukuh Andri (Profesi Pendidikan Dasar, 2015)
The alternative strategy to address social inequality and lack of student learning outcomes are modelsof cooperative learning. There are several models that made the researchers are interested in knowingthe signi.. cance of the difference to the learning outcomes and student activities, namely the model ofSTAD and TGT.The design of this research is quantitative research with this type of quasi-experimentalwith the factorial design version of nonequivalent control group design 2x2 (Tuckman, 1999). Based ondata from pretest and posttest scores can be seen that a good learning outcomes for grade STAD andTGT have increased, the increase amounted to 22.73% STAD class and class TGT by 20.91%. STADclass has increased by 1.82% higher than TGT class. Similarly, in the students’ learning activities,STAD model to get the student activity by 82.44% and amounted to 80.91% of IGT. STAD class rose1.53% higher than TGT class. Based on the hypothesis test concluded that (1) there is no signi.. cantdifference in learning outcomes between the application of the model STAD and TGT, and (2) there is nosigni.. cant difference in learning activities between the application of the model STAD and TGT. Bothmodels are equally able to bene.. t in improving student learning outcomes and student activity. In thisstudy, there is no one model that can be said to be superior significantly from one another.